The OECD Review and Higher Education - Sheffield, Edward; Noah, Harold J.; Hamm-Brucher, Hildegard (Canadian Journal of Higher Education, 1979)
Professor Sheffield tells how the OECD review of educational policies in Canada proceeded, who were involved, and what the examiners stressed in their report. He reports also on a tentative assessment of its impact, most of which is potential or not provable. Professor Noah describes the history and procedures of OECD's reviews of the national education policies of its member states - exercises in the comparative study of education, with practical benefits. Dr. Hamm-Briicher reflects in a highly personal way on her experience as a member of the examining team and her disappointment with the meagre response to the final report on the part of Canadian governments and academics. Nevertheless, she believes strongly in the kind of international co-operation represented by the OECD reviews.